The Decumulation (Payout) Phase of Defined Contribution Pillars : Policy Issues in the Provision of Annuities and Other Benefits - James, Estelle; Vittas, Dimitri (World Bank, Washington, DC, 2014)
Most countries reforming their pension system, focus more on the accumulation phase, than on the decumulation (pay-out), because the number of beneficiaries is likely to be small initially, especially if older workers are discouraged from joining the new system. Policymakers place a priority on the new accumulation system being administratively efficient, and well regulated. But the decumulation phase must also be well organized, and efficient. The purpose of pension systems is, after all, to pay retirement benefits - old age, survivor, and disability pensions. The authors argue that: 1) Pay-out arrangements are likely to evolve gradually, through trial and error, as problems are discovered and tackled. 2) Adverse selection may not be as great a problem as is sometimes thought. 3) Many other annuity, and insurance market problems have yet to be solved, and policies must be formulated to make these markets work as well. The under-development of voluntary annuity markets is only partly explained by adverse selection, argue the authors. Other factors are also at work: the bequest, and precautionary motives for saving; individuals' myopia and ignorance; mistrust of insurance companies; the "luxury good" nature of annuities; tax policies that favor lump sum withdrawals; and, last but not least, public policies (such as the offer of social security pensions and the encouragement of occupational pension plans) that tend to crowd out individual annuities. The long-term success of pension reform depends on vigorous efforts to develop the insurance industry. Weak and under-developed in most developing countries, the insurance industry should play a central role in providing old age, survivor, and disability benefits. Many policy issues require careful thought, and extensive empirical analysis: Should annuitization be mandatory, and at what level? Should indexed (or "real") annuities be required? Should variable annuities be permitted, or encouraged? Should joint annuities be required? How much "group rating" and "risk classification" should be permitted?